Transfer of treatment effects from combined to isolated conditions during functional communication training for multiply controlled problem behavior. Issue 2 (22nd August 2019) - Tsami, Loukia; Lerman, Dorothea C.
Abstract : Functional communication training (FCT) is highly effective for treating socially maintained problem behavior when based on the results of functional analyses (FA). Research suggests that combining relevant antecedents and consequences of problem behavior during FCT can be an efficient approach to treatment for behavior that is multiply controlled. However, no studies have evaluated whether treatment effects under combined conditions would transfer to single, or isolated, conditions. Participants were 5 children with autism, aged 3 years to 6 years, who engaged in problem behavior maintained by both escape from demands and access to tangibles. An experimenter coached their caregivers via video conferencing to implement FA and FCT in their homes. All participants received FCT under a combined condition, followed by brief exposure to sessions with isolated antecedents and consequences. Treatment effects for just 1 of the 5 participants immediately persisted under isolated conditions. These results suggest that, when caregivers combine variables relevant to multiple functions during FCT, exposure to isolated conditions may at least temporarily produce treatment failures.